2019
DOI: 10.1037/xan0000190
|View full text |Cite
|
Sign up to set email alerts
|

The partial reinforcement extinction effect: The proportion of trials reinforced during conditioning predicts the number of trials to extinction.

Abstract: Four experiments compared the extinction of responding to a continuously reinforced (CRf) conditioned stimulus (CS) consistently reinforced on every trial, with extinction of responding to a partially reinforced (PRf) CS that had been inconsistently reinforced. To equate the acquisition of responding between the two CSs, the average duration of the CRf CS was extended so that it scheduled the same overall rate of reinforcement per unit time as the PRf CS. Experiment 1 used a within-subjects design to compare t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(74 citation statements)
references
References 34 publications
7
67
0
Order By: Relevance
“…The probability of reinforcement during training is known to have a scalar effect on trials to acquisition and on trials to extinction (Chan & Harris, 2019;Gibbon et al, 1980). The probability of reinforcement during training is known to have a scalar effect on trials to acquisition and on trials to extinction (Chan & Harris, 2019;Gibbon et al, 1980).…”
Section: The Fundamental Importance Of Computationally Derived Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…The probability of reinforcement during training is known to have a scalar effect on trials to acquisition and on trials to extinction (Chan & Harris, 2019;Gibbon et al, 1980). The probability of reinforcement during training is known to have a scalar effect on trials to acquisition and on trials to extinction (Chan & Harris, 2019;Gibbon et al, 1980).…”
Section: The Fundamental Importance Of Computationally Derived Ratiosmentioning
confidence: 99%
“…The probability of reinforcement during training has a scalar effect on trials to extinction. If on average only 1 in n trials is reinforced during training, it takes nk trials to reach any given extinction criterion, where k is a constant that depends on the criterion (Chan & Harris, 2019;Gibbon, Farrell, Locurto, Duncan, & Terrace, 1980).…”
Section: Numerosity In Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, if the length of each conditioning trial of a CRf CS is three times longer than the length of each conditioning trial of a PRf CS reinforced on one third of trials, then the two CSs will have the same total rate of reinforcement despite a difference in how consistently they were reinforced per trial. Several groups have conducted experiments to test this prediction, and all have failed to support it (Bouton et al, 2014;Chan & Harris, 2017, 2019Harris & Kwok, 2018;Haselgrove, Aydin, & Pearce, 2004). In each case, responding to the partially reinforced CS took longer to extinguish than responding to the consistently reinforced CS.…”
Section: Partial Reinforcement and Extinctionmentioning
confidence: 99%
“…rate of reinforcement during conditioning. I present such an analysis here using the data reported by Chan and Harris (2019). For this analysis, I have used the logarithm of the number of trials to commence extinction for each rat because a preliminary analysis showed that the distribution of trials to extinction was positively skewed and approximated a log-normal distribution (see Figure 3A and 3B).…”
Section: Partial Reinforcement and Extinctionmentioning
confidence: 99%